Short-Term Assessment of Intravitreal Dexamethasone Implant Using Enhanced-Depth Image Optical Coherence Tomography and Optical Coherence Tomography Angiography in Patients with Retinal Vascular Diseases - Minnella, Angelo Maria (Adv Ther, 2018)
INTRODUCTION: To evaluate the short-term efficacy and safety of intravitreal dexamethasone implant (IDI) in patients with macular oedema associated with diabetic retinopathy (DR) and retinal vein occlusion (RVO) using enhanced-depth image optical coherence tomography (EDI-OCT) and to estimate the effect of dexamethasone on the choroid and the retinal vascular network using OCT angiography (OCTA). METHODS: Fifteen eyes in 15 patients with macular oedema secondary to diabetes (DR, n = 8) or retinal vein occlusion (RVO, n = 7) were treated with intravitreal injection of sustained-release IDI. Primary efficacy end points were changes in best corrected visual acuity and central macular thickness (CMT). Secondary end points were changes in choroidal thickness and choroidal and retinal vascular networks as determined by OCTA. RESULTS: CMT was significantly reduced from baseline by 3 h after injection (p < 0.01) and improved further during the 3-month follow-up. Visual acuity improvement was consistent with CMT reduction. No alterations in IOP or systemic side effects were observed. OCTA showed improvement from baseline in terms of decreased number and size of cysts and restoration of the retinal vascular network; flow choroidal thickness did not change significantly. CMT and visual acuity variations were similar in the two groups. CONCLUSIONS: CMT reduced as early as 3 h after the injection of IDI, with further reduction during follow-up. Choroidal thickness was unchanged, whereas the vascular retinal network improved from baseline to the end of study. Both EDI-OCT and OCTA were useful in demonstrating the early beneficial effects of IDI on the macula and the perifoveal vascular network. FUNDING: The article processing charges, the open access fee and the medical writing and editorial assistance was funded by Allergan.